Unapparent microsporidial infection among immunocompetent humans in the Czech Republic - Sak, Bohumil; Brady, Daniel; Pelikánová, Markéta; Květoňová, Dana; Rost, Michael; Kostka, Martin; Tolarová, Věra; Hůzová, Zuzana; Kváč, Martin (Journal of clinical microbiology, 2011)
In the present population-based study, we determined the prevalences of the most common human-pathogenic microsporidia, Encephalitozoon spp. and Enterocytozoon bieneusi, in asymptomatic healthy people living in the Czech Republic. A total of 382 males and females (ages, 1 to 84 years) living in the Czech Republic, of whom 265 were Czech nationals and 117 were foreign students, were included in a study testing for the presence of microsporidia by use of coprology and molecular methods. Single-species infections with Enterocytozoon bieneusi or an Encephalitozoon sp. were detected for 9 and 136 individuals, respectively. Moreover, coinfections were detected for 14 individuals. Four genotypes of 3 human-pathogenic Encephalitozoon spp. and 7 E. bieneusi genotypes, including 3 novel genotypes, were detected. Some of these were reported in humans for the first time. The highest prevalence was recorded for individuals older than 50 years and for loose, unformed stool samples. These findings clearly show that exposure to microsporidia is common among immunocompetent people and that microsporidiosis is not linked to any clinical manifestation in healthy populations.
Keywords: Czech Republic; lidé středního věku; lidé; ženské pohlaví; Female; mužské pohlaví; Molecular Sequence Data; encephalitozoonóza; Asymptomatic Infections; Adult; Sequence Analysis, DNA; Encephalitozoon; Middle Aged; molekulární sekvence - údaje; DNA, Fungal; DNA fungální; sekvenční analýza DNA; Humans; Prevalence; asymptomatické infekce; dospělí; Male; Česká republika; prevalence; Encephalitozoonosis